(untitled) (Research, Society and Development, 2021)
Objective: to analyze the available scientific evidence on the educational and preventive actions of nurses to the person submitted to the colonoscopy examination. Method: this is an integrative review study that aims to summarize the research carried out, the PICO strategy was used, to build the guiding question: What is the evidence available in the literature on the educational and preventive actions of nursing to the patient submitted to colonoscopy? Whose articles were filtered in the databases: LILACS; MedLine; PubMed; SciELO and BDENF. Results: seven studies were selected to compose the review, of which five (n=5) were published in English, which demonstrates a certain weakness and gap in the national publication in relation to the theme. As for the levels of evidence, there was a disparity between the studies developed by foreign nurses and Brazilian nurses, where the national production on the subject is still focused on conducting studies with lower evidence. As for international studies, we were able to identify the predominance of studies with higher levels of evidence (one level I study and four level II studies). Conclusion: it is hoped that the results of this review will contribute to the reflection of the role of nurses in imaging diagnosis sectors, especial lly those who deal with videocolonoscopy, so that they incorporate, reproduce and/or develop educational actions, technologies, new approaches to the user, and especially, will highlight the need for scientific discussion on the expansion of the role of nurses in the prevention of colorectal cancer.